Legends of the Indus - Samina Quraeshi (New York Oxford University Press, 2017)
A modern classic! The five legends of this book are drawn from the main regions of the Indus Valley, a river and valley that stretch from the Himalayas to the desert sands of the Arabian Sea, through a landscape of breathtaking beauty and contrast: Adam & Durkhane from the NW frontier Sohni & Mahiwal from the Northern Punjab Heer & Ranjha from the Southern Punjab Omar & Marui from Baluchistan Sassi & Punnu from Sind Throughout the centuries, passed down from generation to generation, the legends are part of the rich and ancient oral tradition of the region which today lies mostly in Pakistan. They were traditionally told for entertainment and education at community and family gatherings by the Bards and storytellers. They were transposed into verse by the great Sufi poets. They were sung by musicians and they served as inspiration for artist and craftsmen. Such is their appeal in Asia, that they have been turned into major Bollywood films.
Includes Colored Illustrations
Keywords: Legends of the Indus